Perinatal imaging findings of a fetus with Pfeiffer syndrome and a heterozygous c.1019A>G, p.Tyr340Cys (Y340C) mutation in FGFR2 presenting a cloverleaf skull, craniosynostosis and short limbs on prenatal ultrasound mimicking thanatophoric dysplasia type II - Chih-Ping Chen; Jian-Pei Huang; Kun-Shuo Huang; Yi-Yung Chen; Fang-Tzu Wu; Yen-Ting Pan; Chien-Ling Chiu; Wayseen Wang (Elsevier, 2024)
Objective: We present perinatal imaging findings of a fetus with Pfeiffer syndrome and a heterozygous c.1019A>G, p.Tyr340Cys (Y340C) mutation in FGFR2 presenting a cloverleaf skull, craniosynostosis and short limbs on prenatal ultrasound mimicking thanatophoric dysplasia type II (TD2). Case Report: A 37-year-old, gravida 2, para 1, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,XY. However, craniofacial anomaly was found on prenatal ultrasound at 21 weeks of gestation, which showed a cloverleaf skull with severe craniosynostosis and relatively short straight long bones. Fetal magnetic resonance imaging (MRI) analysis at 22 weeks of gestation showed a cloverleaf skull, proptosis and relatively shallowing of the sylvian fissures. Prenatal ultrasound at 24 weeks of gestation showed a fetus with a cloverleaf skull with a biparietal diameter (BPD) of 6.16 cm (equivalent to 24 weeks), an abdominal circumference (AC) of 18.89 cm (equivalent to 24 weeks) and a femur length (FL) of 3.65 cm (equivalent to 21 weeks). A tentative diagnosis of TD2 was made. The pregnancy was subsequently terminated, and a 928-g malformed fetus was delivered with severe craniosynostosis, proptosis, midface retrusion, a cloverleaf skull, broad thumbs and broad big toes. The broad thumbs were medially deviated. Whole body X-ray showed a cloverleaf skull and straight long bones. However, molecular analysis of FGFR3 on the fetus revealed no mutation in the target regions. Subsequent whole exome sequencing (WES) on the DNA extracted from umbilical cord revealed a heterozygous c.1019A>G, p.Tyr340Cys (Y340C) mutation in the FGFR2 gene. Conclusion: Fetuses with a Y340C mutation in FGFR2 may present a cloverleaf skull on prenatal ultrasound, and WES is useful for a rapid differential diagnosis of Pfeiffer syndrome from TD2 under such a circumstance.